Microbial Composition in the Duodenum and Ileum of Yellow Broilers With High and Low Feed Efficiency - Lv, Huijiao; Huang, Yun; Wang, Tao; Zhai, Shangkun; Hou, Zhuocheng; Chen, Sirui (Frontiers in Microbiology, 2021)
The composition of the gut microbiome plays important roles in digestion, nutrient absorption, and health. Here, we analyzed the microbial composition in the duodenum and ileum of yellow broilers. Chickens were grouped based on feed efficiency (high feed efficiency [HFE] and low feed efficiency [LFE] groups; n = 22 each). Microbial samples from the duodenum and ileum were collected, and 16S rRNA sequencing of the V3–V4 region was performed. The dominant bacteria in the duodenum were from the phyla Firmicutes and Cyanobacteria and the genera Lactobacillus, Faecalibacterium, and Ruminococcus. In the ileum, the phyla Firmicutes and Proteobacteria and the genera Lactobacillus, SMB53 and Enterococcus were predominant. Alpha diversity analysis showed that the microbiota diversity was significantly higher in the duodenum than in the ileum. The structure of the ileal microbiota was similar between groups, and the species richness of the microbiota in the HFE group was significantly higher than that in the LFE group. In the HFE and LFE groups, Firmicutes and Cyanobacteria were negatively correlated, and Lactobacillus had medium to high negative correlations with most other genera. Functional prediction analysis showed that the gluconeogenesis I pathway was the most abundant differential metabolic pathway and was significantly altered in the LFE group. Moreover, although the microbial community structures were similar in the duodenum and ileum, the diversity of the microbial community was significantly higher in the duodenum than in the ileum. Pearson correlation analysis revealed that the phylum Chloroflexi and genera Acinetobacter, Pseudomonas, Bacillus and Neisseria were with coefficients < - 0.3 or > 0.3. In the ileum, Ruminococcus may be associated with HFE whereas Faecalibacterium may be associated with LFE. These findings may provide valuable foundations for future research on composition and diversity of intestinal microbes and provide insights into the roles of intestinal microbes in improving feed efficiency and the industrial economic benefits of yellow broilers.